Alterity, Security and Everyday Geopolitics at Israel's Border with Lebanon. Issue 1 (2nd January 2016) - Slesinger, Ian
ABSTRACT: This article reassesses themes in the present literature on borders in political geography by using the case study of Israel's border with Lebanon. This securitized landscape invites a definition of the border predicated on a neat dichotomy between one's own identity and a foreign and dangerous "Other." However even this border is a complex and contradictory boundary, in which residents' attitudes, beliefs and practices are ambivalent and defy neat categorization. This study provides a more nuanced account of geographical imagination at this border by treating the borderland as a heterotopic space, rather than perceiving the border as a fixed line, and by examining the everyday "micro-political" operations and materialities that inhabitants of the border region perform and experience. While there is clearly a relationship between security and identity at this border, the outcome of this research indicates that this relationship is non-linear and more complex than can be allowed for by a hostile cultural imagination solely based on a self/Other dyad.